Failure and success factors of irrigation system developments: A case study from the Oueme and Zou valleys in Benin - Djagba, J.F.; Rodenburg, J.; Zwart, Sander J.; Houndagba, C.J.; Kiepe, P. (Wiley, 2014)
In the period 1960–1980, Chinese and Taiwanese cooperations developed irrigated rice schemes throughout West Africa withvariable success. In Benin for instance, schemes in Zonmon and Bamè (Ouémé Valley) were abandoned upon withdrawal of theproject developers and have been sub-optimally used ever since, while the neighbouring scheme of Koussin-Lélé (Zou Valley) isstill functional (double rice cropping) and well operated and maintained by the farmers. The factors for success and failure were in-vestigated by comparing the two abandoned schemes with the successful one, using ﬁeld observations and stakeholder surveys. Weobserved that (i) operation and maintenance costs associated with irrigation were presumably lower in the successful scheme ––where irrigation was driven by gravity––compared to the failed ones––where part of the schemes were designed for motor-pumpdriven irrigation. Moreover, contrary to the situation in the unsuccessful schemes, farmers in the successful scheme of Koussin-Lélé beneﬁt from (ii) external technical support, (iii) a favourable land tenure policy, entailing seasonal redistribution of plotsfavouring active and motivated producers, (iv) reliable access to credit, and (v) an effective farmer organization. These observationsunderscore the importance of addressing the longer-term technical and ﬁnancial needs of the beneﬁciaries for the successful devel-opment of irrigation schemes advancing smallholder farmers in sub-Saharan Africa.